ELECTROMECHANICAL TRANSITION PROCESS CAUSED BY THE SUDDEN CHANGE IN THE RESULTANT TORQUE OF ACTIVE MECHANICAL FORCES ON THE SHAFT OF THE THREE-PHASE SYNCHRONOUS ALTERNATOR, INITIALLY IN PERMANENT SYNCHRONOUS OPERATION UNDER ELECTRICAL LOAD (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
This paper is an analytical study of the electromechanical transient process occurring in a three-phase synchronous alternator (with a rotor with salient poles) when a small increase in the resulting torque of active mechanical forces is suddenly applied to the alternator shaft—connected to an infinite power electrical network and initially operating in a permanent synchronous mode under electrical load (balanced three-phase). The transient incremental variations of the internal electrical angle (or load) and the electrical angular velocity (rotation) of the rotor are determined. The transient and static stability analysis of the alternator is corroborated by a numerical case study.
Keywords: Electromechanical transient process; Three-phase synchronous alternator